2012
DOI: 10.1593/neo.121534
|View full text |Cite
|
Sign up to set email alerts
|

p53-Independent Roles of MDM2 in NF-κB Signaling: Implications for Cancer Therapy, Wound Healing, and Autoimmune Diseases

Abstract: Murine double minute-2 (MDM2) is an intracellular molecule with multiple biologic functions. It serves as a negative regulator of p53 and thereby limits cell cycle arrest and apoptosis. Because MDM2 blockade suppresses tumor cell growth in vitro and in vivo, respective MDM2 inhibition is currently evaluated as anti-cancer therapy in clinical trials. However, the anti-proliferative effects of MDM2 inhibition also impair regenerative cell growth upon tissue injury. This was so far documented for tubular repair u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 42 publications
1
83
0
3
Order By: Relevance
“…The role of p53 in inflammation has been extensively in experimental animal models especially in reference to non-organ specific autoimmune diseases [36,43,67,68,69]. Systemic p53-deficient mice develop more rapidly collagen-induced arthritis and antigen-induced arthritis [70,71].…”
Section: P53 In Inflammatory and Autoimmune Conditionsmentioning
confidence: 99%
“…The role of p53 in inflammation has been extensively in experimental animal models especially in reference to non-organ specific autoimmune diseases [36,43,67,68,69]. Systemic p53-deficient mice develop more rapidly collagen-induced arthritis and antigen-induced arthritis [70,71].…”
Section: P53 In Inflammatory and Autoimmune Conditionsmentioning
confidence: 99%
“…Therefore, we speculate that the change of p53 protein is caused by post-translation modification of the protein. We analyzed the oncoprotein MDM2, a p53-binding protein that promotes p53 degradation [7,33]. Nevertheless, no significant changes of MDM2 and phosphorylated MDM2 were observed at the early stage of chrysin treatment (Fig.…”
Section: P53 Was Activated By Erk Through Phosphorylation At Ser15mentioning
confidence: 99%
“…The E3 ubiquitin ligase murine double minute-2 (MDM2) regulates proteasomal degradation of the tumor suppressor gene and cell cycle regulator p53 but also, facilitates NF-kB signaling. 5,6 MDM2 overexpression promotes tumor growth, whereas MDM2 antagonists are effective in cancer. 7,8 We have previously shown that MDM2 drives NF-kB signaling-related inflammation in acute tubular injury, whereas its proregenerative effect in the healing phase was exclusively p53-dependent.…”
mentioning
confidence: 99%